How bloggers use geography to develop online destination image for Malaysian Borneo / Siao Fui Wong, Balvinder Kaur Kler and Stephen Laison Sondoh, Jr. - Wong, Siao Fui; Kler, Balvinder Kaur; Laison Sondoh, Stephen (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
This paper provides an understanding of how one single brand effectively represents two places drawing from location branding for tourist destinations. How are images and stories within blogs used to create online destination image (ODI)? A qualitative content analysis (QCA) explored a purposive sample of 25 blogs (in English) to evaluate Malaysian Borneo’s image. The QCA indicates that Sabah and Sarawak are identifiable for unique experiences related to three tourism attributes: nature, adventure, and culture (NAC). Specifically, Sabah is known for its iconic orangutan and Sarawak for its wilderness. This paper contributes to the practical and theoretical development of one brand for two destinations in two ways. First, findings indicate it is possible for one brand to be shared by two competing destinations. Findings also propose bloggers use geographical characteristics to produce an induced image because descriptions and experiences focus on the physical, human-environment, and human geography. The findings of this paper provide a solid foundation for future research to explore the role played by bloggers in creating ODI based on geographical characteristics.